Feeding Practices of Pig Farmers in the districts of Perambalur and Ariyalur in Tamil Nadu - P. Suresh Kumar (The Indian Veterinary Journal, 2025)
The study was taken up to assess the various feeding practices followed by 30 pig farmers in Perambalur and Ariyalur district of Tamil Nadu. It was found that about 57 per cent of farmers used hotel and kitchen wastes and vegetable waste to the pigs reared for fattening purpose, while 30 per cent of the farmers used concentrate feed for breeding pigs with locally available grains. Only 3 per cent of farmers used commercially available swine mash for feeding the animals. Farmers fed pigs with 5-6 kg of hotel waste and kitchen waste per day and also 4 to 5 kg of vegetable waste at evening time. About 10 per cent of the farmers used mixed feeding i.e. concentrate feed, hotel waste and kitchen waste or vegetable waste. It was concluded that most of farmers were not aware of scientific rearing and specific feeding practices, this leads to piglet mortality, low production performance and disease occurrence.